Nursing brain drain from India - Kolenko Mary; Shockness Michelle; Hawkes Michael; Diwaker Krishna (BMC, 2009)
Abstract In response to recent findings regarding migration of health workers out of Africa, we provide data from a survey of Indian nurses suggesting that up to one fifth of the nursing labour force may be lost to wealthier countries through circular migration.